Motivational Factors Influencing Pre-Service EFL Teachers to Choose Teaching as A Future Career - Indah Eka Asriani; Rahayu Apriliaswati; Dwi Riyanti (Universitas Pendidikan Mandalika, 2022)
Motivation to choose teaching profession has a significant role in the professionalism and commitment to the teaching profession. This study investigates motivational factors that influence pre-service teachers of English Education Study Program at FKIP Tanjungpura University, Pontianak to choose teaching as a future career. Unlike the previous research in the Indonesian context that mostly used intrinsic, extrinsic, and altruistic motivation frameworks, this study used a motivational framework by Watt & Richardson (2007) named FIT-Choice Scale. This research was conducted using a survey method. The number of participants in this study is 216 pre-service teachers. By using an online questionnaire that contains close-ended questions adapted from FIT-Choice scale and open-ended questions, the findings show that the main motivational factors that influence the pre-service teachers to choose English teaching as a future career are subject interest (M: 6.13), intrinsic career value (M: 5.78), social utility value (M: 5.75), and prior teaching and learning experience (M: 5.79). Moreover, related to the belief about teaching, the pre-service teachers perceive teaching as a profession with high task demand (M: 5.40), but they rated task return lower (M: 4.91). Furthermore, the researchers also identified other motivational factors mentioned by participants in open-ended questions named religious, personal and professional development, and dual benefit of learning to become an English teacher.